Germinated brown rice ameliorates obesity in high-fat diet induced obese rats - Lim, See Meng; Goh, Yong Meng; Mohtarrudin, Norhafizah; Loh, Su Peng (BioMed Central, 2016)
Background: Germinated brown rice (GBR) is a novel functional food that is high in fiber and bioactive compounds with health-promoting properties. This study aims to evaluate anti-obesity effects of GBR in obese rats fed high-fat diet (HFD). Methods: Male Sprague-Dawley rats were fed HFD for 8 weeks to induce obesity. The rats were then administrated with GBR where the source of dietary carbohydrate of HFD was replaced by either 25 % GBR, 50 % GBR or 100 % GBR for another 8 weeks. Changes in anthropometry, dietary status, biochemical parameters and histopathology of liver and adipose tissue were measured. Results: Rats fed with HFD were showed elevation in body weight gain and in white adipose tissue mass compared with rats consumed commercial diet. The GBR administration in 50 % GBR and 100 % GBR were significantly decreased body weight gains and food intakes as well as improved lipid profiles in obese rats. In addition, the administration of GBR had reduced adiposity by showing declination in white adipose tissue mass, adipocytes size and leptin level concomitantly with a higher ratio of fat excretion into feces. Micro- and macrovesicular steatosis were evidently attenuated in obese rats fed GBR. Conclusion: These findings demonstrated that GBR exhibited anti-obesity effects through suppression of body weight gain and food intake, improvement of lipid profiles and reduction of leptin level and white adipose tissue mass in obese rats fed HFD.